Look into my eyes! Exploring the effect of addressing in educational videos. (June 2017) - Beege, Maik; Schneider, Sascha; Nebel, Steve; Rey, Günter Daniel
Abstract: Numerous studies were conducted to investigate how recipients are affected by the miscellaneous characters in multimedia. However, there is a lack of research concerning the connection between parasocial processes and learning performances. This study aims to investigate the influence of addressing (as a social encounter of parasocial interaction ) on learning performance in an educational video. Addressing was operationalized by manipulating proximity (near vs. far) and orientation (frontal, vs. lateral) of a presented lecturer. We conducted an experiment with 88 participants who were randomly assigned to one of the four experimental groups. Results revealed a large significant orientation effect for retention performance with higher learning outcomes for frontal orientation. Proximity did not significantly influence learning outcomes. Results were interpreted suggesting perceived parasocial interaction which was enhanced in the frontal condition. Parasocial interaction might lead to deeper cognitive processing and affective states which are beneficial for learning. The findings of this study show that learning is fostered by personae in educational learning environments by giving learners the impression to be addressed directly through eye contact. Highlights: Frontal orientation enhances parasocial processes. Study provides the first evidence that addressing of personae is useful to enhance retention performance. Practical implications refer to the presentation of social entities in video based educational environments.